2018
DOI: 10.7554/elife.37131
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar projections in the endolymphatic sac act as a relief valve to regulate inner ear pressure

Abstract: The inner ear is a fluid-filled closed-epithelial structure whose function requires maintenance of an internal hydrostatic pressure and fluid composition. The endolymphatic sac (ES) is a dead-end epithelial tube connected to the inner ear whose function is unclear. ES defects can cause distended ear tissue, a pathology often seen in hearing and balance disorders. Using live imaging of zebrafish larvae, we reveal that the ES undergoes cycles of slow pressure-driven inflation followed by rapid deflation. Absence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 91 publications
0
31
0
Order By: Relevance
“…In the inner ear, pressure is initially regulated by feedback between pressure and lumenal fluid flux. However later in development, we have found that a physical pressure relief valve is necessary for pressure homeostasis in the inner ear (Swinburne et al, 2018). Together, we expect that these new insights on ear development and physiology will be critical to the development of effective clinical therapies for hearing and balance disorders, and for understanding size control in closed epithelial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the inner ear, pressure is initially regulated by feedback between pressure and lumenal fluid flux. However later in development, we have found that a physical pressure relief valve is necessary for pressure homeostasis in the inner ear (Swinburne et al, 2018). Together, we expect that these new insights on ear development and physiology will be critical to the development of effective clinical therapies for hearing and balance disorders, and for understanding size control in closed epithelial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism may involve the transient rupture of tight junctions through mitosis, as in the case of mouse blastocysts (Chan et al, 2019;Leonavicius et al, 2018). Excessive pressure can also lead to a breach of epithelial permeability and pressure relief, as shown in the endolymphatic sac of the inner ear (Swinburne et al, 2018). Other mechanisms may include the active regulation of ion pumping activity and endo-or exocytosis to modulate the lumen volume and pressure, as shown during zebrafish inner ear formation (Hoijman et al, 2015;Mosaliganti et al, 2019).…”
Section: Biomechanical Control Of Luminogenesismentioning
confidence: 99%
“…In addition to creating new mutant models, CRISPR-Cas9 methods have been optimized to create biallelic mutations that enable detection of phenotypes in G 0 CRISPR-Cas9 injected embryos or larvae (Burger et al 2016 ; Hoshijima et al 2019 ; Kroll et al 2021 ; Swinburne et al 2018 ). These CRISPR-Cas9 injected zebrafish are referred to as “CRISPants” or G 0 knockouts.…”
Section: Main Bodymentioning
confidence: 99%